2012
DOI: 10.3892/ijo.2012.1430
|View full text |Cite|
|
Sign up to set email alerts
|

Use of multiple biomarkers for the localization and characterization of colon cancer stem cells by indirect immunocytochemistry

Abstract: Abstract. In this study, we used LGR5, γ-synuclein, p53, KRAS and epiregulin antibodies to localize stem cells by indirect immunocytochemistry in paraffin sections of normal and cancerous colon tissues. In the normal colon tissue, no staining of cells with LGR5, γ-synuclein, p53 and KRAS antibodies was observed, apart from a few scattered cells in between the colon villi that were faintly stained with antibodies to LGR5. Staining of highly differentiated cancer tissue with LGR5 antibodies revealed single cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Moreover, the growth state of the colon can determine the efficiency of polysaccharide hydrolysis [61]. The intake of carbohydrates increases the wet weight of feces resulting in a more relaxed colonic state, which is considered to have a positive impact on colon health [62]. In this study, the protective effect of SCPs on colonic tissue was observed, which was characterized by significantly increase of the colonic index, the length of colon and villi, and the fecal water content in SCP-treated mice compared with those of the control group, suggesting that the intake of SCPs might improve the physiological state of the colon.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the growth state of the colon can determine the efficiency of polysaccharide hydrolysis [61]. The intake of carbohydrates increases the wet weight of feces resulting in a more relaxed colonic state, which is considered to have a positive impact on colon health [62]. In this study, the protective effect of SCPs on colonic tissue was observed, which was characterized by significantly increase of the colonic index, the length of colon and villi, and the fecal water content in SCP-treated mice compared with those of the control group, suggesting that the intake of SCPs might improve the physiological state of the colon.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, immunohistochemical samples are sections of tissue in which each cell is surrounded by tissue architecture and adjacent cells (Javois 1999 ;Amsterdam et al 2012 ). Immunocytochemistry is performed on intact cells with their surrounding extracellular matrix removed.…”
Section: Immunocytochemistry Versus Immunohistochemistrymentioning
confidence: 99%
“…Lgr5 is expressed on Wnt/β-catenin-dependent adult stem cell populations of the intestine, colon and hair-follicle [212]. Expression of Lgr5 has been demonstrated on intestinal crypt stem cells, which are the cells-of-origin of intestinal cancer [213], indicating that Lgr5 is a functional marker of intestinal CSCc involved in intestinal and colorectal carcinogenesis [214,215]. In patients with colorectal cancer, Lgr5 expression positively correlates with histological grade, invasion and metastasis, and inversely correlates with survival of patients, revealing an important role of Lgr5 in the progression and prognosis of colorectal cancer [217].…”
Section: Anti-lgr5mentioning
confidence: 99%